I curse you with joy - Haddish, Tiffany, 1979- (Diversion Books, 2024)
I Curse You With Joy is Tiffany Haddish unfiltered. These essays lay it all bare, bringing readers into Tiffany's inner circle where joy, honesty, humor, and heart are the order of the day.